Pharmacological inhibition of MALT1 (mucosa-associated lymphoid tissue lymphoma translocation protein 1) induces ferroptosis in vascular smooth muscle cells - Binjie Yan; Darrell Belke; Yu Gui; Yong-Xiang Chen; Zhi-Sheng Jiang; Xi-Long Zheng (Cell Death Discovery, 2023)
Abstract MALT1 (mucosa-associated lymphoid tissue lymphoma translocation protein 1) is a human paracaspase protein with proteolytic activity via its caspase-like domain. The pharmacological inhibition of MALT1 by MI-2, a specific chemical inhibitor, diminishes the response of endothelial cells to inflammatory stimuli. However, it is largely unknown how MALT1 regulates the functions of vascular smooth muscle cells (SMCs). This study aims to investigate the impact of MALT1 inhibition by MI-2 on the functions of vascular SMCs, both in vitro and in vivo. MI-2 treatment led to concentration- and time-dependent cell death of cultured aortic SMCs, which was rescued by the iron chelator deferoxamine (DFO) or ferrostatin-1 (Fer-1), a specific inhibitor of ferroptosis, but not by inhibitors of apoptosis (Z-VAD-fmk), pyroptosis (Z-YVAD-fmk), or necrosis (Necrostatin-1, Nec-1). MI-2 treatment downregulated the expression of glutathione peroxidase 4 (GPX4) and ferritin heavy polypeptide 1 (FTH1), which was prevented by pre-treatment with DFO or Fer-1. MI-2 treatment also activated autophagy, which was inhibited by Atg7 deficiency or bafilomycin A1 preventing MI-2-induced ferroptosis. MI-2 treatment reduced the cleavage of cylindromatosis (CYLD), a specific substrate of MALT1. Notably, MI-2 treatment led to a rapid loss of contractility in mouse aortas, which was prevented by co-incubation with Fer-1. Moreover, local application of MI-2 significantly reduced carotid neointima lesions and atherosclerosis in C57BL/6J mice and apolipoprotein-E knockout (ApoE−/−) mice, respectively, which were both ameliorated by co-treatment with Fer-1. In conclusion, the present study demonstrated that MALT1 inhibition induces ferroptosis of vascular SMCs, likely contributing to its amelioration of proliferative vascular diseases.